Macro cultural psychology : a political philosophy of mind - Ratner, Carl. (New York ; Oxford : Oxford University Press, 2012)
This text articulates a bold, new, systematic theory of psychology, culture, and their interrelation. It explains how macro cultural factors are the cornerstones of society and how they form the origins and characteristics of psychological phenomena.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Social psychology; Cognition and culture; Socialization; Psychology